REGIONAL GROWTH DETERMINANTS IN UKRAINE: PANEL DATA ESTIMATES - Shevchuk, Victor (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
In this paper, determinants of real regional per capita growth were estimated using a balanced panel data set consisting of 26 Ukrainian regions for the period from 2002 to 2012. The Arellano-Bond dynamic panel data estimation technique was applied. Among the traditional factors of economic growth, positive effects of investments in physical capital and population growth (for the high-income regions only) were found. Higher inflation and a larger share of rural population are negative regional growth factors, while the depreciation of the real exchange rate and increase in the export of goods has an opposite pro-growth impact. As suggested by the lagged level of the output coefficients, conditional convergence is faster among the high-income regions. The results are robust to the choice of estimators and regression model specifications.